Model Hidrologi Runtun Waktu Untuk Analisis Hujan-Aliran Menggunakan Metode Gabungan Transformasi Wavelet- Ihacres (Studi Kasus : Sub DAS Lubuk Bendahara) - Ardi Wahyudi; Imam Suprayogi; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
IHACRES model is one of the well known rainfall-runoff model and have been successful in investigating the hydrology response of the various watersheds, espencially in indonesia. Previous research in the Rokan Sub-watershed, station AWLR Lubuk Bendahara, Riau Province. The results showed yhat the model IHACRES can be said is still not reliable enough or has not met since the value of R2 generated at simulation stage  at 0,341. It is necessary to further develop an approach using the combined model of wavelet transform – IHACRES with the aim to improve the performance rainfall-runoff model. The results showed that the best scheme in the calibration phase is scheme 1 (3 years calibration) a significant increase in overall input data is filtered in the form of rain data, climatology and streamflow using wavelet transform wherein R2 value of 0,369. While the results of statistical tests of coreelation coefficient (R) indicates that the Haar wavelet model of level 2 increased by 0,03 compared to the original data without filtering by value respectively 0,645 and 0,642. This value is considered a strong correlation. The results showed the use of wavelet transform – IHACRES proviede enhanced performance rainfall-runoff model.  Keyword : wavelet haar, wavelet transform, rainfall- runoff, IHACRES model